BIOLOGICALS AND BIOSIMILAR: ADVANCING HEALTHCARE THROUGH INNOVATION AND ACCESSIBILITY - Pal, Pradeep; Chorasiya, Anjali; Jawani, Akanshag; Rathore, Chalsy; Panwar, Mangal Singh (Journal of Global Pharma Technology, 2025)
“Biologics” considered one of the fastest growing sectors of the pharmaceutical industry; “Biologics” have introduced many new treatments for life-threatening and rare diseases. The first generation of bio pharmaceutical products produced using recombinant technologies was launched in the 1980s and is now on the way to patent expiration. As a result, research and generic pharmaceutical companies are seizing the opportunity to develop “generic” substitutes for original biologics, referred to here as biosimilars. However, the process of introducing an innovator's biosimilar product is much more complex than the relatively straightforward process of introducing a generic equivalent of an innovator's product based on a new chemical entity. Biologics are produced by cells in culture or whole organisms, which are inherently more variable than chemical synthesis methods. Therefore, unlike generic drugs, it is not possible to create an identical or identical copy of the innovator product. In this way, biosimilars are "similar but not the same" or in other words biosimilars are "a twin but not a clone" of the original biologic innovator product. The field of biosimilars therefore presents several important challenges, including i) validation of similarity, ii) interchangeability of biosimilar and innovative products, iii) possible need for a unique nomenclature to distinguish different bio pharmaceutical products, iv) regulatory framework, v) business opportunities as well as guidance for assistance to manufacturers in product development, vi) intellectual property rights and vii) public safety. Keywords: Biosimilars, Biological drugs, Innovative product, Pharmacovigilance.